A comparative quality study and energy saving on intermittent heat pump drying of Malaysian edible bird's nest. Issue 1 (2nd January 2017) - Gan, Shu Hui; Ong, Sze Pheng; Chin, Nyuk Ling; Law, Chung Lim
ABSTRACT: This paper aims to study the influence of temperature and relative humidity (RH) during intermittent heat pump drying at 28.6–40.6°C, 16.2–26.7% RH, α = 0.2–1.0, and the comparison was made against fan drying (27°C, 39.7% RH, α = 1.00). It was observed that the effects of temperature and RH on drying rate were significant when moisture content was high. Experimental results showed that intermittent heat pump drying at 28.6°C, 26.7% RH, α = 0.2 of edible bird's nest greatly reduced effective drying time by 84.2% and color change compared to fan drying, and retained the good energy efficiency.